Key brain cell interactions and contributions to the pathogenesis of Alzheimer’s disease - Saavedra, Joana; Nascimento, Mariana; Liz, Márcia A.; Cardoso, Isabel (Frontiers in Cell and Developmental Biology, 2022)
Alzheimer’s disease (AD) is the most common neurodegenerative disease worldwide, with the two major hallmarks being the deposition of extracellular β-amyloid (Aβ) plaques and of intracellular neurofibrillary tangles (NFTs). Additionally, early pathological events such as cerebrovascular alterations, a compromised blood-brain barrier (BBB) integrity, neuroinflammation and synaptic dysfunction, culminate in neuron loss and cognitive deficits. AD symptoms reflect a loss of neuronal circuit integrity in the brain; however, neurons do not operate in isolation. An exclusively neurocentric approach is insufficient to understand this disease, and the contribution of other brain cells including astrocytes, microglia, and vascular cells must be integrated in the context. The delicate balance of interactions between these cells, required for healthy brain function, is disrupted during disease. To design successful therapies, it is critical to understand the complex brain cellular connections in AD and the temporal sequence of their disturbance. In this review, we discuss the interactions between different brain cells, from physiological conditions to their pathological reactions in AD, and how this basic knowledge can be crucial for developing new therapeutic strategies.